Phase changing materials in building elements - Ermolli, Sergio Russo (2011)
New technologies in building construction and services are needed in order to reduce the big energy consumption in the building stock from which a major part goes for controlling of indoor climate. On the other hand, performance requirements are growing higher because of both more severe regulations and higher comfort requirements by the users – the wide use of air conditioning systems, also in houses, is just an example of this trend. Integration during the design phase among Architecture, Building Technology and Services is thus much recommended to obtain a more sophisticated “living-environment”, using relatively simple strategies and avoiding extra-costs. It is possible to tackle the problem of energy consumption with stratified lightweight skins and layers, high performance materials and integration of installations, like heat pumps for example or wind turbines, and enhancing the use of renewable energy sources by using devices like solar photovoltaic panels or solar thermal exchanger or simply by preferring natural ventilation and natural shading or re-interpreting low processing materials and using them in a clever way.